2018
DOI: 10.1101/454520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultra-sensitive measurement of brain penetration with microscale probes for brain machine interface considerations

Abstract: Microscale electrodes are rapidly becoming critical tools for neuroscience and brain-machine interfaces (BMIs) for their high spatial and temporal resolution. However, the mechanics of how devices on this scale insert into brain tissue is unknown, making it difficult to balance between larger probes with higher stiffness, or smaller probes with lower damage. Measurements have been experimentally challenging due to the large deformations, rapid events, and small forces involved. Here we modified a nanoindentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 41 publications
4
46
0
Order By: Relevance
“…This causes problems if the maximal force is below the force needed for insertion. Measurements have been made for different types of electrodes (Sharp et al, 2009;Casanova et al, 2014;Fekete et al, 2015), and recently a quantitative study was undertaken to understand the penetration mechanics of microwires specifically (Obaid et al, 2018). In our experiments, 15-20 μm wires could be inserted into the cortex several millimetres deep without support.…”
Section: Discussionmentioning
confidence: 99%
“…This causes problems if the maximal force is below the force needed for insertion. Measurements have been made for different types of electrodes (Sharp et al, 2009;Casanova et al, 2014;Fekete et al, 2015), and recently a quantitative study was undertaken to understand the penetration mechanics of microwires specifically (Obaid et al, 2018). In our experiments, 15-20 μm wires could be inserted into the cortex several millimetres deep without support.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum free length was limited by the material properties and buckling force threshold of the microwires. For example, 18 µm diameter tungsten wires with lengths of > 5 mm are feasible, while for 20 µm gold wires, lengths greater than 3 mm are likely to buckle upon insertion 41 . Different tip shapes are also possible through polishing or etching the ends of the wires (Fig S3eg).…”
Section: Microwire Bundlesmentioning
confidence: 99%
“…Alternatively, the wires could be individually electrosharpened 42 to form a <100 nm radius tip, then bundled together afterwards. Studies measuring the force of microwire insertion into brain tissue have found microwire size and electrosharpening play an important role in the amount of brain dimpling during insertion 41 .…”
Section: Microwire Bundlesmentioning
confidence: 99%
“…Maximum insertion force was measured at the time of penetration, which was taken as the first absolute maximum of the force curve that preceded the first approximately infiniteslope curve characteristic of membrane penetration (Sridharan et al, 2013, Obaid et al, 2018. In a few cases, a slightly higher force was measured after initial penetration.…”
Section: In Vivo Insertion Force Measurementsmentioning
confidence: 99%
“…For a shuttle made of a given material, with length determined by the depth of the target brain area, a lower limit on the allowable device diameter is calculable by Euler's critical load equation. A larger diameter device will have a higher critical load to more likely penetrate the meninges, but is not desirable because it will compress a greater area of brain tissue on insertion and disrupt more vasculature (Obaid et al, 2018). One way to enable insertion of a device without increasing its diameter is to reduce the effective force on the device (i.e., to lower the required insertion force) by fabricating a sharper tip (Sharp et al, 2009, Bjornsson et al, 2006, Edell et al, 1992, Jensen et al, 2006.…”
Section: Introductionmentioning
confidence: 99%